Activity of Bangle Rhizome Extract (zingiber cassumunar roxb.) Inhibits the Growth of Trichophyton rubrum and Trichophyton mentagrophytes - Inderiati, Dewi; Widhyasih, Retno Martini; Aryadnyani, Ni Putu; Warditianin, Ni Kadek; Astuti, Ketut Widyani (Politeknik Kesehatan Kemenkes Jakarta II, 2023)
Bangle rhizome extract (zingiber purpureum roxb.) is a herbal plant that is widely consumed in Indonesia. Bangle rhizome extract (zingiber purpureum roxb.) has broad medical properties such as diuretic, anti-hypertension, brochodilator, immunomodulator, analgesic, anti-inflammatory, anti-oxidant, anti-tumor, anti-diabetic, anti-microbial and anti-fungal. The aim of this research was to determine the yield results of extracts using the solvents Aquadest, Aceton, Ethanol 70%, Ethanol 96% and Methanol. And to find out the results of phytochemical screening tests and active ingredient content using GCMS. The stages of this research include the extraction process, phytochemical screening test and GCMS. The results of research on the yield of Bangle rhizome extract with the five solvents obtained the largest yield, namely with distilled water, 7.2 percent. Based on the phytochemical screening test, Bangle rhizome extract was positive for containing secondary metabolites such as tannins, alkaloids, triterpenoids, steroids and saponins. The lowest MIC results for Bangle extract were in Aquadest solvent at 6.25 mg/mL with a value of 0.049 mg/mL and continued in 70% Ethanol solvent with a value of 3.125 mg/mL in the fungus Trichophyton rubrum and in the fungus Trichophyton mentagrophytes with an MIC value of 3.125 mg/mL. while the highest MIC value was obtained in the solvent acetone, Ethanol 96%, Methanol with a value of 0.049 ml/ML for both fungi.